A társadalmi szakmablokk változása - Csákó, Mihály (Szociológiai Szemle, 2024)
In the 60s and 70s the Hungarian skilled worker training institutions served as channels for the massive upward intergenerational mobility of the children of layers with agricultural and unskilled industrial occupation. In 1974 the occupations could be grouped according to their role played in this process of mobility in the first national sociological survey of apprentices. At that time five social occupational blocs could be isolated right from the ’occupations of entry’, serving as the lowest gate of the world of skilled work, to the elite occupations. Our survey, conducted twenty years later, shows that with the exception of the ’bloc of the occupations of entry’ the social blocs of occupations have lost their sharp outlines. Today the majority of apprentices come from families of skilled workers, thus for them learning a trade has a different significance from the one it had for the former generation. Changes fit into the explanatory framework of falling social mobility and increasingly rigid stratification, further on, the influence of the return to the market economy should also be considered.